894. Clinical utility of methicillin resistant Staphylococcus aureus (MRSA) nasal PCR to streamline antimicrobial use in the treatment of diabetic foot infection (DFI) with or without osteomyelitis (OM). (15th December 2022) - Harb, Gaielle; Hopkins, Teri L; Yang, Linda; Morneau, Kathleen; Frei, Christopher R; Cadena-Zuluaga, Jose; Walter, Elizabeth
Abstract: Background: DFI guidelines recommend empiric MRSA-targeted therapy in settings of high prevalence or severe infection; however, they do not provide recommendations for de-escalation. This approach has the potential to increase unnecessary use of broad-spectrum antibiotics; therefore, additional strategies are needed to optimize appropriate antibiotic use. This study evaluates the effect of MRSA nasal PCR testing on MRSA-targeted antibiotic use and clinical outcomes in patients with DFI. Methods: This was a retrospective quasi-experimental study of patients > 18 years admitted to South Texas VA for DFI, with or without OM, who had an MRSA nasal PCR and culture data. Eligible patients were identified from the Corporate Data Warehouse and reviewed via electronic health record. Patients were allocated into two groups: PRE (5/1/2019-4/30/2020) and POST (12/1/2020-11/30/2021) protocol implementation for de-escalation or avoidance of MRSA-targeted antibiotics. The primary outcome was median (interquartile range [IQR]) days of inpatient MRSA-targeted antibiotic therapy. A Wilcoxon Rank Sum test was used to assess the difference between the groups for the primary outcome. Secondary outcomes included the proportion of patients needing MRSA coverage added back after de-escalation, hospital readmission, length of hospital stay (LOS), patient mortality, and acute kidney injury. Results: A total of 151 patients were included (83 PRE; 68 POST). Most patients were male (98% PRE; 97% POST) with a median age of 64 (IQR, 56-72) years. There was a significant decrease in MRSA-targeted antibiotic therapy use, from a median of 72 (IQR, 27-120) hours in the PRE group, to 24 (IQR, 12-72) hours in the POST group (p < 0.01). There was also a significant decrease in hospital readmission from 17% in the PRE group to 5% in the POST group (p = 0.02). No significant differences were found for other secondary outcomes. Conclusion: This study of patients presenting to a VA hospital with DFI identified a statistically significant decrease in median duration of MRSA-targeted antibiotic use post-protocol implementation. This suggests a favorable effect of MRSA nasal PCR for de-escalation or avoidance of MRSA-targeted antibiotics in DFI. Disclosures: All Authors : No reported disclosures.